The relationships and diversification of Ordovician and Silurian chilidiopsoidean brachiopods. (2nd August 2016) - Cocks, L. Robin M.
Abstract : Within the brachiopod Suborder Orthotetidina, only members of the Superfamily Chilidiopsoidea are of Ordovician and Silurian ages, and the earliest ( Eocramatia and Gacella ) are Middle Ordovician (Darriwilian). Their ancestry is obscure; it may have lain either within the Orthida, since the Chilidiopsoidea all have impunctate shells, or within the Strophomenoidea, since many chilidiopsoids have a supra-apical pedicle foramen. Gacella is the only chilidiopsoid externally similar to the related Superfamily Triplesioidea. There are now four families in the Chilidiopsoidea, with two genera in the Eocramatiidae, nine in the Chilidiopsidae, a single Silurian genus within the Areostrophiidae and only Gacella within the Gacellidae, which is upgraded from subfamilial to familial status here. Within the Chilidiopsidae, although Valdaria has a distinctive shape, the remainder ( Chilidiopsis, Coolinia, Fardenia, Krizistrophia, Magicostrophia, Morinorhynchus and Saughina ) have been confused or synonymized by previous authors, and thus their type species are redescribed here. In particular, Orthis applanata, the type species of the much-quoted Coolinia, and Schuchertella pertinax, the type species of Saughina, have not been revised in modern terms since their erection in 1846 and 1917, respectively. As well as the type species of the genera listed above, the extensively cited Coolinia pecten (Linnaeus, 1758) is also redescribed. Two new genera, Portrania and its new species P. wrighti Cocks & Harper from the Late Katian Portrane Limestone of Ireland, and Scalenomena, with type species Fardenia scalena Williams, 1962, from the Early Katian Craighead Limestone of Girvan, Scotland, are erected. The genus Krizistrophia Havlíček, 1992, is considered a juvenile of Morinorhynchus and is thus synonymized with it, and Terazkia Havlíček & Štorch, 1990, which was described from the same Motol Formation (Wenlock) of the Czech Republic, is considered a nomen dubium. Chilidiopsis itself, which has often been synonomized with Coolinia, is recognized as a distinct genus. http://zoobank.org/urn:lsid:zoobank.org:pub:630E7168-319F-40ED-9CFD-81096FF10811